The structural basis of MRI bone erosions: an assessment by microCT. Issue 8 (19th September 2012) - Albrecht, Andreas; Finzel, Stephanie; Englbrecht, Matthias; Rech, Jürgen; Hueber, Axel; Schlechtweg, Philipp; Uder, Michael; Schett, Georg
Abstract : Objective: To determine whether erosions appearing in MRI in patients with rheumatoid arthritis (RA) represent true erosions. Methods: 50 RA patients received 1.5 T MRI and microCT (μCT) of the dominant hand. Erosion counts were assessed in coronal T1 weighted MRI sections and in coronal as well as axial μCT sections of the metacarpophalangeal (MCP) joints II–IV. Extent of erosions was assessed by RA MRI Score (RAMRIS) erosion score (MRI) and by three-dimensional assessment of erosion volume (μCT). Results: 111 of the 600 evaluated joint regions showed erosions in the MRI and 137 in the μCT. In only 28 regions false negative lesions (μCT positive, MRI negative) were found, all of which were very small lesions with a volume of less than 10 mm 3 . Only two results were false-positive (μCT negative, MRI positive). RAMRIS erosion scores were strongly correlated to erosion volumes in the μCT (Pearson's r=0.514, p<0.001). Mean RAMRIS erosion scores were below 1 with erosion volumes up to 1.5 mm 3, below 2 with erosion volumes up to 20 mm 3 and over 2 with volumes of more than 20 mm 3 . Discussion: MRI erosions are generally based on true cortical breaks as shown by μCT. MRI is sensitive to detect bone erosions and only very small lesions escape detection. Moreover, RAMRIS erosion scores are closely linked to the absolute size of bone erosions in the μCT.